Motywy wiejskie w polskich piosenkach (po II wojnie światowej) - Chańko, Jan (Zeszyty Wiejskie, 2016)
The author made an attempt to present the different aspects of village life described in lyrics of Polish songs. The analysis was based upon sources from the Internet such as: Biblioteka Polskiej Piosenki, Tekstowo.pl. and Teksty.org. Some features of the author are related to melody, rhythms and arrangement of the songs described in the analysis. The author emphasizes the educational impact of songs. The material was carefully selected and divided into seven groups of topics: a) “mechanical” group - containing songs with words such as: village, villages, hamlet, including descriptions regarding to towns and cities, b) village propaganda and the alliance between city and village, c) rock and roll with countryside tune; d) attempts to describe reality of village life; e) satirical songs regarding villages, f) “masterpieces” of Polish disco g) remaining compositions. In every category there are quotations from the most significant songs. The author draws a conclusion that the most popular are first two groups of songs, hence those are the most important source of inspiration for artists.